1999
DOI: 10.1007/bf02359357
|View full text |Cite
|
Sign up to set email alerts
|

Residual strength of pipelines with dents

Abstract: We show the urgency of developing methods for prediction of the ultimate load of ductile fracture for defects of the dent type in pipelines. We propose an idealized model of the limiting plastic state of a pipe with infinite dent along it. We obtain formulas for engineering calculations and analyze them.Present-day methodologies of evaluation of the strength of very plastic materials [ 1,2] demand that one carry out calculations by the methods of limit equilibrium. However, the evaluation of defects in pipelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For the dented metallic pipe, Orynyak et al (1999) developed a simple analytical equation to predict the bursting strength with respect to dimensionless length of dent (λ = l d / √ Rt). However, only a single dimension of dent was taken into account.…”
Section: Prediction Of Bursting Capacitymentioning
confidence: 99%
“…For the dented metallic pipe, Orynyak et al (1999) developed a simple analytical equation to predict the bursting strength with respect to dimensionless length of dent (λ = l d / √ Rt). However, only a single dimension of dent was taken into account.…”
Section: Prediction Of Bursting Capacitymentioning
confidence: 99%
“…The research found that the collapse capacity of pipes was relatively insensitive to the detailed geometry of a dent such as the shape and size, but was critically dependent on the maximum ovalisation of its most deformed cross-section. Orynyak et al (1999) developed an ana-lytical equation to predict the bursting strength with respect to dimensionless length of dent (λ l = l d / √ Rt). Bjørnøy et al (2000) investigated the bursting capacity of dented pipes subjected to internal pressure through experiments.…”
Section: Introductionmentioning
confidence: 99%